Growth Indices among Children and Adolescents with Type 1 Diabetes - Baghdad – Iraq, 2013 - Abd-Alrazak, Ounse M.; Ghalib, Batool A.; Abduljabbar, Hana A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Type 1 diabetes mellitus is one of the most common chronic endocrine disorders of childhood, growth impairment is one of its long−term consequencesObjective: To study the anthropometric indices among children with type 1diabetes.Results: A total of 253 children with type 1diabetes were studied, 51.8% were females, 47.9% developed the disease at 5-9 years of age, and 52.6% presented with classical signs and symptoms. Stunting /sever stunting was 15% with male predominance, higher among older age group (10-20 y), wasting/ sever wasting was 19.4% with male predominance, higher among older age group (10-20 y), over weight/ obese was 3.6% with females predominant and higher among younger age group.Patients and Methods: All children with type 1diabetes attending Diabetic Clinic at Children Welfare Teaching Hospital-Baghdad, during 1/1 – 31/5/2013were included in this cross sectional study. Demographic data, disease information, and type of presentation were obtained directly through patient's interviews. The weight in kilogram and height in centimeter were measured for each child and their anthropometric indices were classified according to World Health Organization indicators, 1997.Conclusion: Wasting/ sever wasting and stunting /sever stunting were the highest growth problems among diabetic children with male predominance and higher among older age group at diagnosis.